Variable face milling to normalize putter ball speed and maximize forgiveness - Lambeth, J.; Brekke, D.; Brunski, J. (Proceedings, 2018)
The forgiveness of golf putters is traditionally achieved through weight distribution. Higher MOI (moment of inertia) putters will show less ball speed loss on impacts away from the sweet spot. A very large MOI putter, however, may not be desired by a golfer due to weight or appearance. The relationship between ball speed and impact location is affected by the mass properties of the putter (i.e., CG location, mass, moments of inertia, products of inertia) and the putter face. It has been shown that certain face properties, such as milling patterns, grooves, or soft inserts, can have small effects on ball speed. This paper proposes a method to normalize the ball speed on laterally miss-hit putter impacts using a "model-specific" milling pattern of variable depth and pitch, resulting in the largest possible region of the face providing consistent putt distances, thus improving performance given the average player`s impact pattern.